Health and Socio-economic Implications of Poverty in Bangladesh - Sacchidanand Majumder; Soma Chowdhury Biswas (European Scientific Journal, ESJ, 2018)
The objective of this study was to explore the influences of the health and socio-economic factors associated with the poverty level of households in Bangladesh, through an analysis of data from the Household Income and Expenditure Survey (HIES) 2010 conducted by Bangladesh Bureau of Statistics (BBS). A total of all 12,240 households was considered in this study. CBN method was applied for estimating poverty of the household. A logistic regression analysis was used to identify the main factors that influence the household’s poverty. The results showed that the probability of the household being poor was higher when the household’s head suffered from various chronic diseases like chronic fever, injuries/disability, eczema, leprosy, and asthma/breathing trouble as compared to the household whose head didn’t suffer from any chronic diseases. From the analysis, it was also found that when a large number within household suffered from any chronic disease, the probability of the household being poor was increased. The household that had no access to health care was poorer than the household that had access to health care. The results also showed that with increased investment in health, the probability of the household being poor was decreased. The results showed that rural households were poorer than urban households. Monthly income, land ownership, construction materials of walls and roofs, types of the latrine, source of drinking water, household size; age, sex, and employment status of the household’s head all had a significant impact on the poverty level of the household.